The role of free vitamin D and vitamin D binding protein in SARS‐Cov‐2 infection in children - US, MAHMUT CANER (My University, 2023)
Background: Many studies have discussed the effects of serum vitamin D deficiency in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) patients. This study aimed to investigate the relationship between SARS-CoV-2 infection severity and free vitamin D (FVD) and bioavailable vitamin D (BAVD) levels in children. Methods: A prospective case–control study design was used. Participants were divided into three groups based on the World Health Organization COVID-19 Clinical Progression Scale. Serum 25-hydroxyvitamin D (ng/mL), albumin (g/L), and vitamin D binding protein (ng/mL) levels were evaluated to investigate the relationship between disease severity and FVD and BAVD levels. Results: In total, 82 participants were included in the study. Of those, 24.4% were uninfected (n=20), 50% had a mild case of SARS-CoV-2 (n=41), and 25.6% had a moderate case (n=21). There was a statistically significant difference in FVD and BAVD levels between the groups (p=0.026). Median FVD (p=0.007, Cohen's d=0.84) and BAVD (p=0.007, Cohen's d=0.86) levels were significantly higher in the mild group compared to the moderate group. FVD and BAVD metabolites were moderately positively correlated with lymphocyte counts (FVD: r=0.437, p<0.001; BAVD: r=0.439, p<0.001). Conclusions: This is the first study to demonstrate a relationship between SARSCoV-2 symptom severity and FVD and BAVD levels. The relationship between FVD and BAVD levels and lymphocyte counts could play an important role in symptom severity and should be evaluated in further studies.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); child; SARS-COV-2; vitamin D; vitamin D binding protein; vitamin D deficiency